Corporate Governance, Environmental Disclosure,dan Kepemilikan Keluarga - zulfikar, rudi (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2016)
The objective of this study is to examine : (1) the impact of corporate governance on environmental disclosure (2) the impact of corporate governance on environmental disclosure with family ownership as the moderating variable. The sampel of this study consist of 84 observations from manufactur company which listed in Indonesia Stock Exchange from 2011 to 2013. Multiple regression analysis is used to test the hypothesis in this research.The result of this study show that the impact of corporate governance has significant influence toward environmental disclosure. But, family ownership as the moderating variable inrelation between corporate governance and environmental disclosure has not significant influence.  Keywords : corporate governance, enviromental disclosure, kepemilikan keluarga